Time-motion analysis of the football World Cup in Russia 2018 - Peev, P.; Tsvetkov, V.; Youroukov, N. (Journal of Applied Sports Sciences, 2019)
The focus of the research is the motion characteristics of the teams which participated in the World cup 2018 in Russia. For the purpose of the research we collected the data from all the matches in the knock out phase of the tournament. We divided the results for every position during the halves and calculated the total distance covered. This way we could get an idea of the intensity and the profile of elite soccer players. In the analyses we included 273 players that played in the knock out phase. As a result of the research, we found that the goalkeeper had total distance covered of 4061,59 meters; defenders had a 9352 meters; midfielders had a 10708 meters and strikers had a 9731 meters. It is interesting that the total distance covered during the second half is greater than in the first one. Conclusion of the research is that the total distance covered is different for all of the researched positions which is a predisposition for disclosing the motor profile of the players. From the study of motor activity in football at world championships we can draw the following conclusions:1) The results are comfirmation that even at a World Cup the performance characteristicsare greatly influenced by position of play; 2) The higher total distance covered during the second half suggests extremely high aerobic capabilities of elite football players.